FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN TERHADAP KONSUMSI BUAH JERUK SIAM DAN PEPAYA DI KECAMATAN BATURAJA TIMUR (JASEP, 2018)
Factors Affecting Consumers Against Consumption of Siam And Papaya Fruits in East Baturaja Subdistrict. This study aims to analyze consumer demand for consumption of citrus fruit and papaya. The method used in this research is the survey method, with a sample of 60 respondents. Sampling method used in this research is Accidental Random Sampling. The type of data used is primary data and secondary data. Method of data processing using multiple linear regression analysis. The results showed that the significant effect on consumption of Siam Citrus fruit in eastern baturaja district is price, income, age and education level. While factors that significantly affect the consumption of Papaya fruit is the price, income, age and education level.